The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ol.2015.3415
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of combining VEGFA, FLT1 and KDR mRNA expression in lung cancer

Abstract: Abstract. Angiogenesis is important in cancer progression. Promising results in clinical trials have indicated that targeting vascular epidermal growth factor (VEGF) signaling may prolong lung cancer patient survival. In particular, various studies have implicated VEGFA as a potential prognostic marker in lung cancer, although prognostication using the expression of VEGF receptors (VEGFRs), such as fms-related tyrosine kinase 1 (FLT1; also known as VEGFR1) and kinase insert domain receptor (KDR; also known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…Our previous report showed that combining VEGFA , FLT1 , and KDR expression could be a better prognostic indicator in lung cancer compared to when these factors were considered individually. 29 In the present study, we have shown that using similar methodology, this three-gene signature is a robust prognostic indicator in colon cancer. Most importantly, this three-gene signature has been shown to predict the response to bevacizumab, an anti-angiogenic agent.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our previous report showed that combining VEGFA , FLT1 , and KDR expression could be a better prognostic indicator in lung cancer compared to when these factors were considered individually. 29 In the present study, we have shown that using similar methodology, this three-gene signature is a robust prognostic indicator in colon cancer. Most importantly, this three-gene signature has been shown to predict the response to bevacizumab, an anti-angiogenic agent.…”
Section: Discussionmentioning
confidence: 60%
“… 7 Antiangiogenic therapy is also a successful strategy in the treatment of lung cancer patients; 27 , 28 we recently reported that a VEGFA-FLT1-KDR gene signature had strong prognostic significance in lung cancer patients. 29 In the present study, we investigated the prognostic significance of the combined mRNA expressions of VEGFA , FLT1 , and KDR in colorectal cancer using colon cancer datasets available in the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic value of this receptor expression in NSCLC remains controversial. In several recent studies, an unfavorable effect of high VEGFR1 expression on NSCLC patient' survival has been demonstrated (87,49), whereas others found no correlation between the expression and the prognosis of the disease (88). To resolve discrepancies in the results further investigations are needed.…”
Section: Discussionmentioning
confidence: 98%
“…VEGFA in tumors has also been studied in breast cancer, 67 , 68 laryngeal carcinoma, 69 colorectal cancer, 70 , 71 bladder cancer, 72 and lung cancer. 73 In PC, Liu et al 74 found that VEGFA was involved in the Twist/miR-497/VEGFA axis, which is significantly correlated to metastasis and angiogenesis in PC. VEGFA secretion has also been reported to be regulated by myoferlin and affects tumor-associated angiogenesis in PC.…”
Section: Discussionmentioning
confidence: 99%